ENHANCING LANGUAGE SKILLS AND ENVIRONMENTAL LITERACY: AN ECO-PEDAGOGICAL APPROACH TO TEACHING ENGLISH TO YOUNG LEARNERS - Özcan, Eda Nur; Gürsoy, Prof. Dr Esim (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study investigates the integration of an eco-pedagogical approach into a language course designed for young learners of English through theme-based language instruction and ESD (Education for Sustainable Development). With the growing concern regarding environmental sustainability in global education, there is an urgent need to equip learners with necessary skills and knowledge to educate responsible citizens of future. This need is particularly crucial to young learners who are at critical ages during which shaping attitudes and behaviors bears lifelong benefits in terms of influencing their future environmental actions and decisions. English as the global language can be an empowering tool since language lesson offers a great range of flexibility in terms of selection of topics and themes while presenting linguistic forms and functions in an authentic context. Drawing on an interdisciplinary perspective, the study proposes practical suggestions on how to design an ESD-based language course with an environmental theme focus for young learners in an EFL (English as a Foreign Language) context along with course design strategies and creating digital materials and offering action-oriented in-class activities to grow young learners into active agents who can identify global and local environmental problems and suggest environmental-friendly solutions. The study also discusses benefits and challenges of the integration and offers recommendations for teachers and curriculum developers in EFL contexts. Overall, this study advocates for an interdisciplinary perspective that aims to foster environmental literacy skills and language skills of young learners by providing hands-on guidance for language teaching professionals.